Clinical features and genetic spectrum of Chinese patients with hereditary spastic paraplegia: A 14-year study - Yu, Weiyi; He, Ji; Liu, Xiangyi; Wu, Jieying; Cai, Xiying; Zhang, Yingshuang; Liu, Xiaoxuan; Fan, Dongsheng (Frontiers in Genetics, 2023)
Background: Hereditary spastic paraplegia (HSP) constitutes a group of clinically and genetically rare neurodegenerative diseases characterized by progressive corticospinal tract degeneration. The phenotypes and genotypes of HSP are still expanding. In this study, we aimed to analyse the differential diagnosis, clinical features, and genetic distributions of a Chinese HSP patients in a 14-year cohort and to improve our understanding of the disease. Methods The clinical data of patients with a primary diagnosis of HSP at the initial visit to the Department of the Neurology, Peking University Third Hospital, from 2008 to 2022 were retrospectively collected. Next-generation sequencing gene panels (NGS) combined with a multiplex ligation-amplification assay (MLPA) were conducted. Epidemiological and clinical features and candidate variants in HSP-related genes were analyzed and summarized. Results 54 cases (probands from 25 different pedigrees and 29 sporadic cases) from 95 patients with a primary diagnosis of HSP were finally confirmed to have a clinical diagnosis of HSP based on clinical criteria, including their clinical findings, family history and long-term follow-up. Earlier disease onset was associated with longer diagnostic delay and longer disease duration and was associated with a lower risk of loss of ability to walk independently. In addition, 20 candidate variants in reported HSP-related genes were identified in these clinically diagnosed HSP patients, including variants in SPAST, ALT1, WASHC5, SPG11, B4GALNT1, and REEP1. The genetic diagnostic rate in these 54 patients was 35.18%. Conclusion Hereditary spastic paraplegia has high clinical and genetic heterogeneity and is prone to misdiagnosis. Long-term follow-up and genetic testing can partially assist in diagnosing HSP. Our study summarized the clinical features of Chinese HSP patients in a 14-year cohort, expanded the genotype spectrum, and improved our understanding of the disease.